Pemikiran ekonomi Yusuf Al-Qaradlawi - laili, anis nur (Maliki Interdisciplinary Journal, 2025)
Yusuf al-Qaradlawi is a contemporary scholar who plays a major role in shaping modern Islamic thought, especially in the fields of Islamic jurisprudence, social, and economics. Through the maqashid sharia and moderation (wasathiyah) approaches, al-Qaradlawi offers an ijtihad method that combines the strength of classical tradition with sensitivity to the dynamics of the times. In the field of Islamic economics, he emphasized the importance of values ​​and morals in economic activities, and developed the concept of professional zakat that is relevant to the conditions of modern society. He also contributed to explaining tax law, usury, and Islamic banking through the maqashid fiqh and social justice approaches. His extensive and in-depth work proves his contribution as a multidimensional scholar, whose thoughts remain relevant and an important reference for contemporary Muslims.